Analisis Pengendalian Kualitas Produk Mengunakan Metode Taguchi dan FMEA di PT Raharjo Perkasa Multikarya - Miftah Siraj, Danu; Suhendar , Endang (Jurnal Indonesia Sosial Sains, 2022)
PT Raharjo Perkasa Multikarya was first established in 2015, under the name PT. Multipurpose Continent or Concrete Continent. Based on the results of observations, it was found that the quality of management of the company was found to be a factor of disability originating from delays in arriving raw materials, operator errors and untimely mixing. It is known from calculations using the FuzzyFMEA method with FRPN values. As for the existing failures, it occurred in Rank 1 of 72900 with failures occurring due to operator error, Rank 2 of 57600 with failures occurring because the mixing process was not carried out on time, and Rank 3 of 51200 with failures occurring due to delays in the arrival of raw materials. Calculations in the second study were carried out using the Taguchi method from values ​​calculated with the help of Qualitek-4 and FMEA software. The research objective was carried out to optimize product quality, and also to provide input for improvement in the cast concrete mix process. Based on the results of the FRPN the following are (Rank 1), namely the results obtained on the identification of the risk of failure carried out by operator error, namely 72900. And based on calculations using the Taguchi method of cast concrete mix, namely with a guide weight of sand 980 (kg), weight of cement 30 (kg), stirring time 450 (seconds), volume in water 40 (liters) and gravel weight 5 (kg). With the aim to minimize the category of defects. In other words, the determination of the desired quality characteristics in the cast concrete mix the lower the number of defects categories produced in the production process, the less so that customer demands can be fulfilled.